RELASI KETERAMPILAN MEMBACA KRITIS DAN BERPIKIR LOGIS DENGAN KUALITAS PENULISAN SKRIPSI KUANTITATIF MAHASISWA PENDIDIKAN AGAMA ISLAM STIT PEMALANG - Mar’atul Lutfiyah (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2019)
Abstract This study aims to: (1) determine the relationship between criticalreading skills and the quality of PAI students' quantitative thesis writing, (2)find out the relationship between logical thinking and PAI Student'squantitative thesis quality, (3) find out the relationship between criticalreading skills and logical thinking together with the quality of quantitativethesis writing for PAI students. This research is a quantitative research witha design of product moment correlation analysis and multiple linearregression. The study was conducted at the Pemalang Tarbiyah College ofSciences (STIT). The population is 100 students. The sample was taken byproportionate stratified random sampling of 65 students. Data was collectedthrough questionnaires. Data analysis includes descriptive analysis, testinganalysis prerequisites, and hypothesis testing. The results showed that: (1)there was a positive and significant relationship between critical readingskills and the quantitative quality of PAI students' thesis, (2) there was apositive relationship and significance between logical thinking and PAIStudent's quantitative thesis quality, (3) positive and significance betweencritical reading skills and logical thinking with the quality of quantitativethesis writing for PAI students. This means that the quality of quantitativethesis writing of PAI (Y) students can increase by improving critical readingskills (X1) and the ability to think logically (X2).Keywords: critical reading, logical thinking, and quantitative thesis